Reasons for lesion uncrossability as assessed by intravascular ultrasound. Issue 7 (14th April 2022) - Salem, Hanan; Mintz, Gary S.; Matsumura, Mitsuaki; Zhang, Mingyou; Usui, Eisuke; Seike, Fumiyasu; Fujimura, Tatsuhiro; Noguchi, Masahiko; Hu, Xun; Jin, Ge; Li, Chenguang; Fall, Khady N.; et al.
Abstract: Objectives: The purpose of the current study was to use intravascular ultrasound (IVUS) to clarify anatomical and morphological lesion characteristics of uncrossable lesions. Background: Uncrossable lesions are not always severely calcified. The prevalence of uncrossable lesions that are nonseverely calcified as well as other mechanisms for uncrossability has not been well clarified. Methods: A total of 252 de novo uncrossable lesions in native coronary arteries that underwent either rotational or orbital atherectomy due to inability of any balloon to cross the lesion and 38 lesions with severe calcium in which IVUS crossed preatherectomy were included. Severe calcium is defined as maximum arc of calcium ≥270°. Results: Severe calcification was absent in 16% of uncrossable lesions, 83% of which had a significant vessel bend. Compared with crossable lesions with severe calcium, uncrossable lesions with severe calcium more often had a bend in the vessel (71% vs. 21%, p  < 0.001) and a longer length of continuous severe calcium (median length of calcium ≥270° 3.8 mm vs. 1.9 mm, p  = 0.001). Other than severe calcium (especially long continuous calcium) or a bend in the vessel, anatomical factors associated with uncrossabilty were aorto‐ostial lesion location and small vessels. Conclusions: Uncrossable lesions are not always severely calcified. The interaction of lesion morphology (continuous long and large arcs of calcium) and vessel geometry (bend in the vessel or ostial lesion location) affect lesion crossability.